Changes in illicit drug use and markets with the COVID‐19 pandemic and associated restrictions: findings from the Ecstasy and Related Drugs Reporting System, 2016–20. (16th July 2021) - Price, Olivia; Man, Nicola; Bruno, Raimondo; Dietze, Paul; Salom, Caroline; Lenton, Simon; Grigg, Jodie; Gibbs, Daisy; Wilson, Tanya; Degenhardt, Louisa; Chan, Roanna; Thomas, Natalie; et al.
Abstract: Aims: To describe (i) self‐reported changes in drug use and (ii) trends in price, perceived availability, and perceived purity of illicit drugs, among people who regularly use ecstasy/ 3, 4‐methylenedioxymethamphetamine (MDMA) and other illicit stimulants in Australia following COVID‐19 and associated restrictions. Design: Annual interviews with cross‐sectional sentinel samples conducted face‐to‐face in 2016–19 and via video conferencing or telephone in 2020. Data were collected via an interviewer‐administered structured questionnaire. Setting: Australian capital cities. Participants: Australians aged 16 years or older who used ecstasy/MDMA and other illicit stimulants on a monthly or more frequent basis and resided in a capital city, recruited via social media and word‐of‐mouth ( n  ~ 800 each year). Measurements: Key outcome measures were self‐reported illicit drug market indicators (price, purity and availability) and, in 2020 only, perceived change in drug use (including alcohol and tobacco) since March 2020 and reasons for this change. Findings: For most drugs, participants reported either no change or a reduction in their use since COVID‐19 restrictions were introduced. Ecstasy/MDMA was the drug most frequently cited as reduced in use ( n  = 552, 70% of those reporting recent use), mainly due to reduced opportunities for socialization. While market indicators were largely stable across most drugs, the odds of perceiving MDMA capsules as 'high' in purity decreased compared with 2016–19 [adjusted odds ratio (aOR) = 0.72, 95% confidence interval (CI) = 0.53–0.99], as did perceiving them as 'easy' to obtain (aOR = 0.42, CI = 0.26–0.67). The odds of perceiving cocaine and methamphetamine crystal as 'easy' to obtain also decreased (aOR = 0.67, CI = 0.46–0.96 and aOR = 0.12, CI = 0.04–0.41, respectively). Conclusions: After COVID‐19‐related restrictions were introduced in Australia, use of ecstasy/MDMA, related stimulants and other licit and illicit drugs mainly appeared to remain stable or decrease, primarily due to impediments to socialization.